Sexual dysfunction in women in the postpartum period: literature review (Research, Society and Development, 2020)
Most women return to sexual activity within three to six months after delivery, however, in the first three months sexual dysfunction is common in a large part of this population, decreasing at six months, and most of the time complaints of dyspareunia and loss of desire. This study aims to investigate sexuality in the puerperium. This is a literature review, which carried out searches in the Lilacs, PubMed and Bireme databases. Articles in Portuguese, English and Spanish were included. As a result, 134 articles were found, of which 17 were selected for review. From the studies analyzed, it can be concluded that the mode of delivery does not influence sexual dysfunction, however, it can influence the psychological factor due to situations in which the puerperal woman passed during childbirth, in addition, all women should be oriented on return to sexual activity, especially primiparous women.